Comparison of Pattern Electroretinography and Optical Coherence Tomography Parameters in Patients with Primary Open-Angle Glaucoma and Ocular Hypertension - Semra Tiryaki Demir; Mehmet Ersin Oba; Ezgi Tuna Erdoğan; Mahmut Odabaşı; Ayşe Burcu Dirim; Mehmet Demir; Efe Can; Orhan Kara; Selam Yekta Şendül (Türk Oftalmoloji Dergisi, 2015)
Objectives: To investigate the correlation of visual field (VF), pattern electroretinography (PERG) and Fourier domain optical coherence tomography (FD-OCT) results in patients with ocular hypertension (OHT) and early primary open-angle glaucoma (POAG). Materials and Methods: The study included 72 eyes of 37 patients with early POAG, 76 eyes of 38 patients with OHT, and 60 eyes of 30 controls. All subjects underwent full ophthalmologic examination, VF assessment with 24-2 Humphrey standard automated perimetry (Swedish Interactive Thresholding Algorithm (SITA)-Standard), retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thickness measurement with FD-OCT, and PERG P50 and N95 wave latency and amplitude measurements with electroretinography (Nihon Kohden). Results: With the exception of the nasal quadrant, all GCC parameters and RNFL results were significantly lower in the POAG group compared to the OHT and control groups. There was no statistically significant difference between the OHT and control group. PERG amplitudes were lower in the POAG and OHT groups than in the control group. Reduction in N95 amplitude was greater than that of P50 amplitude. No difference was detected in PERG latencies among groups. GCC was significantly correlated with VF and RNFL in the POAG group. Conclusion: Significant thinning of the GCC and RNFL occurs in addition to VF pathologies in patients with early POAG, and these examinations should be concomitantly evaluated. During diagnostic assessment of patients with early POAG, GCC and RNFL analysis by FD-OCT are highly effective. GCC is as reliable as RNLF in the early diagnosis of glaucoma and there is a highly significant correlation between them. Dysfunction of ganglion cells in patients with OHT may be detected earlier using PERG amplitude analysis.